(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This study tries to investigate the impact of surgical strike in the form of demonetization done by PM Narendra Modi to curb black money from Indian Economy before and after demonetisation on Indian Banking sector for the period of 1st Sept 2016- 11th January 2017.Event Study Methodology has used where the Cumulative Average Abnormal Returns (CAAR) of the stock prices of select private and public sector banks listed on NSE India in different event windows have been analysed. A paired sample t-test has been conducted to compare the pre-announcement and post-announcement returns of stock prices for the event window i.e., Demonetisation.